PENGGUNAAN MEDIA TORSO UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ORGAN PENCERNAAN DI SD NEGERI BOJONGJENGKOL 03 KABUPATEN BOGOR - Lili Fajrudin; Khoerunnisa Nur Awaliah Rahmat; Yusup Junaedi (Journal of Professional Elementary Education, 2022)
This study aims to determine the implementation of the use of learning media using Torso media in improving student learning outcomes in science lessons on the subject of Digestive Organs in Theme 3 Sub-theme 1. The research method used is Kurt Lewin's CAR (Classroom Action Research) with the following steps: (1) planning, (2) action, (3) observation, and (4) reflection. From the results obtained in the pre-cycle learning, it can be seen that only 8 students have completed the KKM with a percentage of 36% with an average value of 62.27. Then proceed to cycle 1 and get a score that only 12 students have completed the KKM with a percentage of 55% with a class average of 67.27. After that, cycle 2 was carried out again with the score that 22 students all completed the KKM with a percentage of 100% with a class average of 90.00. Thus there has been an increasing change so there is no need to take further action because it has been successful. Based on all these data, it can be concluded that using the demonstration method can improve student learning outcomes in Natural Science Subjects Theme 3 Sub-theme 1 in class V SD Negeri Bojongjengkol 03 Ciampea District, Bogor Regency, West Java Province